Front Pembela Islam (FPI) sebagai Kekuatan Oposisi pada Masa Pemerintahan Joko Widodo Tahun 2014 - 2020 - Waty, Reni Rentika; Kamarudin, Kamarudin (Indonesian Democracy Research Center, 2022)
FPI (Islamic Defenders Front) is a social organization that has consistently positioned itself as the opposition since the reform era. However, during Jokowi's administration, the attitude of the FPI opposition was more dominant compared to the government before Jokowi. Using Robert A. Dahl's opposition theory and Maurice Duverger's pressure group theory, as well as qualitative methods, this research wants to see the reasons for FPI positioning itself as the opposition, find out the form of FPI's oppositional stance and FPI's affiliation with Joko Widodo's (Jokowi) political opponent, then analyze the relationship between between ideological and political aspects of FPI's oppositional stance during Jokowi's administration. The results of this study show that the FPI oppositional movement is divided into two, namely the FPI oppositional movement based on ideological aspects and based on political aspects. This includes proselytizing, political support for Jokowi's opponents and pressure movements such as the 212 Movement.